Factors Influencing the Evaluation Process of Teacher Professional Allowance Policy - Tuilan, Jeane; Basikin (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this study is the performance allowance of the teacher. The purpose of this research is to find out the factors influencing the evaluation process of teacher professional allowance policy (a study at SMP Negeri 2 Tomohon). This research is expected: (1). To be able to develop concepts of public policy theory, especially regarding Teacher Professional Allowance Evaluation Policy in Tokyo City (2). To be able to increase knowledge about public policy concepts and evaluation, especially being critical in responding to various public problems that occur around us. The researchers took SMP Negeri 2 Tomohon as the research location and used qualitative research, which was conducted in a natural setting, and the data collected was generally qualitative. The results were several factors: (1). The effectiveness that when the teacher has status as a professional, of course, he should also have to work professionally by adjusting with developments, both in terms of ability in the preparation of the material and the mastery of technology as well; (2). Efficiency: this professional allowance is a policy step taken by the government to improve academic qualifications and competencies and to increase the level of welfare of teachers. This study recommends further research on teacher professional competence in Tokyo City.